A Viking Market Kingdom in Ireland and Britain - Horne, Tom.
1 online resource (274 pages).
Keywords: Viking-Age trade, network theory, silver economies, kingdom formation, and the Scandinavian raiding and settlement of Ireland and Britain are all popular subjects. However, few have looked for possible connections between these phenomena, something this book suggests were closely related. By allying Blomkvist's network-kingdoms with Sindbæk's nodal market-networks, it is argued that the political and economic character of Viking-Age Britain and Ireland - my 'Insular Scandinavia' - is best understood if Dublin and Jórvík are seen as being established as nodes of a market-based network kingdom. Based on a dataset relating to the then developing bullion economies of the central and eastern Scandinavian worlds and southern Scandinavia in particular, it is argued that war-band leaders from, or familiar with, 'Danish' markets like Hedeby and Kaupang transposed to Insular Scandinavia the concept of polities based on establishment of markets and the protection of routeways between them. Using this book, readers can think of interlinked Dublin and Great Army elites creating an Insular version of a Danish-style nodal market kingdom based on commerce and silver currencies. A Viking Market Kingdom in Ireland and Britain will help specialist researchers and students of Viking archaeology make connections between southern Scandinavia and the market economy of the Uí Ímair ('descendants of Ívarr') operating out of the twin nodes of Dublin and Jórvík via the initial establishment of Hiberno-Scandinavian longphuirt and the related winter-camps of the Viking Great Army.